1996
DOI: 10.1074/jbc.271.1.505
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor Stimulates Protein Kinase A through a Mitogen-activated Protein Kinase-dependent Pathway in Human Arterial Smooth Muscle Cells

Abstract: The abilities of platelet-derived growth factor (PDGF) and insulin-like growth factor (IGF-I) to regulate cAMP metabolism and mitogen-activated protein kinase (MAP kinase) activity were compared in human arterial smooth muscle cells (hSMC). PDGF-BB stimulated cAMP accumulation up to 150-fold in a concentration-dependent manner (EC 50 Ϸ 0.7 nM). The peak of cAMP formation and cAMP-dependent protein kinase (PKA) activity occurred approximately 5 min after the addition of PDGF and rapidly declined thereafter. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 50 publications
(55 reference statements)
10
56
1
Order By: Relevance
“…PGE 2 is one of the principal growth-inhibitory prostaglandins secreted by human SMCs (23). PGE 2 secretion into the culture medium was determined as previously described (24). For immunoblotting experiments, lysates from cells incubated with PDGF-BB for 5 min with or without a 30-min preincubation with 10-30 M PD 098059 or 10 M indomethacin were used for immunoblotting and detection of cPLA 2 band shift due to phosphorylation as described (24).…”
Section: Methodsmentioning
confidence: 99%
“…PGE 2 is one of the principal growth-inhibitory prostaglandins secreted by human SMCs (23). PGE 2 secretion into the culture medium was determined as previously described (24). For immunoblotting experiments, lysates from cells incubated with PDGF-BB for 5 min with or without a 30-min preincubation with 10-30 M PD 098059 or 10 M indomethacin were used for immunoblotting and detection of cPLA 2 band shift due to phosphorylation as described (24).…”
Section: Methodsmentioning
confidence: 99%
“…Are the signal transduction pathways activated by the IGF-IR that lead to directed migration different from those that lead to proliferation? Early studies using human SMCs suggested that IGF-I stimulation did not activate MAPK in this cell type (Takagi et al 1995, Graves et al 1996, Koyama et al 1996. However, others reported an increase in MAPK activity after IGF-I treatment in rat SMCs (Thommes et al 1996).…”
Section: The Multiple and Redundant Intracellular Igf Signaling Pathwmentioning
confidence: 96%
“…44,45,[62][63][64][65][66] Ras is capable of activating both Raf [67][68][69] and Mekk; 70 however, activation of the Erk pathway can also occur in the absence of Ras activation. 71 The pathways leading to Erk activation are reported to be triggered by receptor tyrosine kinases, 72,73 G-protein linked receptors, [74][75][76] PKC, 71,77,78 and calcium. 46,[79][80][81][82] Several lines of evidence suggest that the Erk pathway has an important role in modulating the survival of hematopoietic cells.…”
Section: The Ras/raf/mek/erk Signaling Kinase Cascadementioning
confidence: 99%